RELATIONSHIPS BETWEEN COMMUNICATION SATISFACTION, JOB SATISFACTION AND JOB PERFORMANCE – A REVIEW OF IMPORTANT EMPIRICAL RESEARCHES SINCE 1970 - Milanović, Vesna M.; Dragičević-Radičević, Tatjana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2020)
Communication, job satisfaction and job performance are important factors of organizational business success. Communication can improve job satisfaction and this way it can increase work motivation. Therefore, the aim of this paper was to present the significant findings regarding the relationships between communication satisfaction, job satisfaction and job performance that researchers report on since 1970. Five studies (i.e. meta-analyses) that tested the relationship between job satisfaction and job performance and 12 studies that tested the impact of communication satisfaction on both job satisfaction and job performance were selected (search by key terms in databases ScIndex and Google Scholar. The results of the original studies of the meta-analyses mostly indicated that a low or inconsistent relationship exists between job satisfaction and job performance. However, all of the meta-analyses confirmed that a significant and moderate relationship exists between these variables. The relationship is not weak (the correlation is not low) as it has long been considered. Conformity of the constructs, the same way of observing and measuring the variables, and adequate method of reliability estimates of performance ratings (the inter-rater reliability) gave more reliable results and stronger correlation. As there was a lack of consistency in testing the same variables as moderators in the original studies, it was difficult to determine the moderators of this relationship. The empirical studies confirmed that a significant and strong relationship exists between communication satisfaction and both job satisfaction and job performance. Besides, job satisfaction–job performance relationship was moderated by communication dimensions such as accuracy of information and lateral communication. Reconsidering the relationships between these variables should remain an important research topic in order to determine the nature of these relationships and the conditions under which these variables are related.